Дослідник руху граматичних форм і фразеобіограф (до ювілею професора Л.І. Коломієць) - Колоколова, А.; Трифонов, Р. (Iнститут української мови НАН України, 2009)
The article is devoted to the jubilee of Professor L.I.Kolomiyets’, a language historian. It contains biographical information about her and a survey of her scientific works.